Decline Curve Analysis of Continuous Injection Gas Lifted Wells - DANIEL, Ayodele; AKEJU, Mercy O.; ISEHUNWA, Sunday O.; ADEYI, Abel A.; OGUNYEMI, Adebayo T. (FUDMA Journal of Engineering and Technology, 2026)
Decline Curve Analysis is one of the established techniques for reservoir performance evaluation and estimation of developed reserves. While it has been well utilized for natural drive production, there have been challenges in accurate evaluation of gas lifted wells because of additional energy that supplements the natural which changes future production rate of the reservoir and distorts the reservoir’s production decline trend. For continuous gas lifted wells, several attempts have been made to model production rates, but none have been found to be simple or accurate. In this article the principle of superposition has been applied such that the production rate of a well at a time, t after gas-lift has been introduced would be the sum of the flow rate due to the natural flow and gas-lift induced flow rate. Four actual well production data sets obtained from the SPE Data Repository and from reservoirs in literature from Niger Delta were used to assess the model. The analysis done included cases with and without gas lift and statistical analysis was done to evaluate the error margin. The equation derived is a mathematical model in which the traditional Arps’ exponential model accounts for the natural flow and a power law model accounts for the gas-lift induced flow expressed as:           q_t=q_inf 〖[e〗^(-Dt)+βt^(-λD)]                  The model proposed showed that 0.48MMstb, 0.31MMstb, 8.75MMstb, and 1.23MMstb respectively would be produced when gas-lift is introduced as opposed to 0.26MMstb, 0.16MMstb, 7.96MMstb, and 1.10MMstb without gas-lift respectively, from well 1 to 4. The model also predicted future rates that were similar to the actual field data with correlation coefficient of 0.884, 0.806, 0.917, and 0.874 respectively. This statistical result indicates the effectiveness of the model in predicting the production decline rate of gas-lifted wells.
Keywords: Decline curve analysis, Developed reserves, Production rate, Gas lift, Arps’ exponential model.